A Pilot Study on Motivations of Amateurs in the Community Saxophone Ensemble in Singapore - Ho, Leslie Wong Kah (Harmonia: Journal of Arts Research and Education, 2025)
Through the realization of The Singapore Band Project, Singapore has developed a thriving wind music initiative in school music education and ensemble playing training. Nevertheless, the problem of engaging participants in music-making beyond their school remains a critical issue, as in most cases, only about 10% of each cohort continues to be engaged in the activity. This pilot study employed a quantitative methodology to investigate the musicians of two single-instrument ensembles in Singapore: The Protégé Saxophone Ensemble and the Music Elements Saxophone Ensemble. The demographic data and ongoing engagement motivational factors are as follows. The study evaluates the Motivators of Continued Participation as outlined by Krause in her 2020 study and the hierarchy of these Motivators through sentiment scoring. The findings reveal that intrinsic motives are the most significant for long-term engagement and continued participation in music making during emerging adulthood. The results aim to provide recommendations for developing sustainable recruitment and retention strategies to support music ensembles and continue growing the vibrant music community in Singapore. Therefore, this study helps to close the gap between academic music education and adult music participation, emphasizing the necessity of an individualized program approach.